New direction in research on extraction of Citrus aurantifolia (lemon fruit) essential oil grown in Mekong Delta - Vietnam via microwave-assisted hydrodistillation - Tran, Thien Hien; Nguyen, Van Tien; Dao, Tan Phat; Lam, Tri Duc; Toan, Tran Quoc; Nguyen, Trinh Duy; Vo, Dai-Viet N.; Vy, Tran Anh; Bui, Le Minh (IOP Publishing, 2019)
A new research approach has been applied to the extraction of lemon essential oils to increase the extraction efficiency and improve the quality of isolated essential oils. In this study, the combination of microwave extraction method and response surface method is employed to investigate factors influencing lemon peel essential oil extraction process; including size of the raw material particles, raw material to water ratio, extraction time, and microwave power. The results showed that lemon peel of sizes 1 to 2 mm, material: solvent ratio 1:3 g/mL, extraction time of 60 min and microwave power of 450 W gave the highest yield of essential oil (2.4 %). The GC-MS results showed the domination of D-Limonene, the main ingredient of citrus essential oils, in higher concentrations than those reported by previous studies.